Nanochitosan antimicrobial activity against Streptococcus mutans and Candida albicans dual-species biofilms - Ikono, Radyum; Vibriani, Agnia; Wibowo, Indra; Saputro, Kurniawan Eko; Muliawan, Wibias; Bachtiar, Boy Muchlis; Mardliyati, Etik; Bachtiar, Endang Winiati; Rochman, Nurul Taufiqu; Kagami, Hideaki; Xianqi, Li; Nagamura-Inoue, Tokiko; et al. (BMC Research Notes, 2019)
Chitosan nanoparticle (nanochitosan) has a broad antimicrobial spectrum against diverse pathogenic microorganisms. However, its effect on dental caries-associated microorganisms, such as Streptococcus mutans and Candida albicans is yet to be explored. These microorganisms are known for causing early childhood caries. Therefore, this study was aimed at investigating nanochitosan inhibition capacity against dual-species biofilms of S. mutans and C. albicans. In this study, nanochitosan antimicrobial activity is reported against mono and dual biofilm species of S. mutans and/or C. albicans at 3 and 18 h incubation time. Nanochitosan inhibition capacity was observed through biofilm mass quantity and cell viability. The present study successfully synthesized nanochitosan with average diameter of approximately 20-30 nm, and also established dual-species biofilms of S. mutans and C. albicans in vitro. With nanochitosan treatment, the cell viability of both microorganisms significantly decreased with the increasing concentration of nanochitosan. There was no significant decrease in biofilm mass both in the dual and single-species biofilms after 3 h of incubation. However, greater inhibition of biofilm was observed at 18 h incubation.